East of Eden Movie Still - Warner Bros.:::Creator::::::::::::
Sam the Sheriff (Burl Ives) sits as Adam Trask (Raymond Massey) stands to his left. They are against the wall of a building partially blocking out writing on the wall. RESTRICTED USE